Mangrove ecosystems in Western Asia: a literature review of trends, conservation gaps, and sustainable management strategies - Yap, Chee Kong; Al-Mutairi, Khalid Awadh (Frontiers in Forests and Global Change, 2025)
This study conducts a comprehensive bibliometric and systematic literature review (SLR) of mangrove ecosystem research in Western Asia, adhering to PRISMA guidelines to ensure methodological rigor. A total of 168 eligible documents published between 1991 and 2025 were identified from key Middle Eastern countries, including Saudi Arabia, Iran, the United Arab Emirates, Oman, Qatar, and Bahrain. The analysis synthesizes key trends in mangrove research across themes such as biodiversity conservation, climate change adaptation, socio-economic impacts, and sustainable management. Using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework, four key strengths were identified: ecological resilience of Avicennia marina, growing research productivity, institutional collaboration, and policy interest. Weaknesses included fragmented governance, limited socio-economic valuation, and inadequate data integration. Opportunities were found in emerging technologies such as remote sensing, blue carbon finance, and regional restoration programs. Threats were dominated by climate change, industrial encroachment, and transboundary pollution. To translate these findings into actionable strategies, a TOWS matrix was developed. The Strength–Opportunity (SO) strategy proposed leveraging robust research capacity to access climate finance and promote innovation. The Weakness–Opportunity (WO) strategy emphasized applying geospatial tools to overcome governance gaps. The Strength–Threat (ST) strategy suggested using localized pollution data to enhance regulatory enforcement. Finally, the Weakness–Threat (WT) strategy advocated for the development of cross-border policy networks to mitigate shared ecological risks. By integrating bibliometric insights with strategic planning tools, this study provides evidence-based recommendations for improving mangrove governance, monitoring, and conservation in the arid coastal zones of Western Asia.